Impact on venous haemodynamics after treatment of great saphenous vein incompetence using plethysmography and duplex ultrasound. (August 2020) - Nelzén, P Oskar E; Skoog, Johan; Öster, Malin; Zachrisson, Helene
Objectives: To evaluate postoperative venous haemodynamics and quality of life after treatment of great saphenous vein (GSV) incompetence. Methods: Radiofrequency ablation and high ligation and stripping were performed in 62 patients (65 limbs) and 58 (65 limbs), respectively. Phlebectomies were performed in both modalities. Strain-gauge plethysmography on the foot combined with superficial venous occlusion was used to measure refilling time after knee bends. Strain-gauge plethysmography, duplex ultrasound and quality of life were assessed before and one month after treatment. Results: Duplex ultrasound displayed successful intervention in all but two limbs. Refilling time increased similar in radiofrequency ablation and high ligation and stripping after treatment ( p < 0.001). Postoperatively, strain-gauge plethysmography detected remaining reflux in 71% of the patients. Multivariate analysis showed that two or more incompetent calf branches were associated with remaining reflux (OR 4.82 (95% CI: 1.33–17.5), p = 0.02). No difference in quality of life was seen in patients with remaining reflux. Conclusions: Despite successful treatment, a majority of the limbs showed remaining reflux, in which incompetent calf branches appear to play an important role. Clinicaltials.gov: Lower Limb Venous Insufficiency and the Effect of Radiofrequency Treatment Versus Open Surgery. Nr: NCT02397226